Systemic infection of Staphylococcus aureus in postnatal woman: a unique finding - Prasanthi, Annie; Mathews, Jiji Elizabeth; Bharathy, Muruga; Rathore, Swati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Staphylococcus bacteraemia is the leading cause of hospital acquired and community acquired bacteraemia. Complications associated are difficult to recognise. Mortality is 20 to 40%. This is a unique case discussing the metastatic spread of Staphylococcus infection following a wound infection. An informed consent was taken from the patient before publishing this case report.